Cardiotoxicity associated with carfilzomib: systematic review and meta-analysis. Issue 11 (2nd November 2018) - Shah, Chintan; Bishnoi, Rohit; Jain, Ankur; Bejjanki, Harini; Xiong, Sican; Wang, Yu; Zou, Fei; Moreb, Jan S.
Abstract: Carfilzomib is a second-generation proteasome inhibitor (PI) that is approved for patients with relapsed or refractory multiple myeloma (RRMM) who failed ≥1 prior lines of therapy. We performed a systematic review of carfilzomib literature with meta-analysis to determine cumulative incidence of cardiotoxicity. After the literature search, we included a total of 29 eligible phase I/II, phase II and phase III clinical trials which used carfilzomib. The cumulative incidence and overall odds ratios (OR) were calculated with random effect model, using 'R' software with metaphor package. A total of 4164 patients with various malignancies were included. The overall estimated cumulative incidence of cardiotoxicity was 8.68% and 4.92%, respectively, for all-grade and high-grade (≥ grade 3) toxicity, which seems higher than other PIs. Compared to control group, the odds of developing cardiotoxicity due to carfilzomib was significantly higher with OR of 2.03 (95% CI: 1.19–3.46, p  = .010) and 2.04 (95% CI: 1.31–3.17, p  = .002) for all-grades and high grades, respectively. Concomitant immunomodulatory agents seem to increase the risk of cardiotoxicity (high-grade cardiotoxicity 6.45% and 4.34% with and without concomitant immunomodulatory agents, respectively ( p  = .033)). There was no variation in the incidence of cardiotoxicity among newly diagnosed versus RRMM ( p  = .38), and high versus standard dose carfilzomib ( p  = .86).